Flashover Characteristics of Dry Band-water band on Hydrophobic Surfaces - Xiaohan Wu; Fanghui Yin; Bin Cao; Daiming Yang; Shichao Shao; Liming Wang (CSEE Journal of Power and Energy Systems)
Due to their outstanding anti-flashover characteristics, composite insulators have been extensively applied in power systems. A lot of research has investigated flashover characteristics of hydrophobic specimens with artificial water droplets. However, the phenomenon is not consistent with that of the contaminated composite insulators. On the test specimens covered with water droplets, there is no obvious leakage current before the flashover and no obvious relationship between flashover voltage and the conductivity of water droplets. On the contaminated composite insulator surface, there are short continuous arcs on the insulators before critical flashover, making insulators look like a luminous lantern. Considering that under these two conditions, the proportion of water along the insulation distance is different, the flashover characteristic of “dry band-water band” on a hydrophobicity surface is analyzed in the present study. The influence of the water band parameter (including length, width, and conductivity) as well as the length of dry band is studied. On this basis, the arc generation and development process of the surface covered with “dry band-water band” is analyzed. The research results improve the understanding of the flashover process on contaminated composite insulators.